Common Fixed Point Theorem for Multivalued Mappings Using Ternary Relation in G-Metric Space with an Application - Lucas Wangwe (Abstract and Applied Analysis)
This paper proves a common fixed point theorem for single-valued and multivalued mappings by using ternary relation in G-metric spaces. Henceforth, results obtained will be verified with the help of illustrative examples. Also, we demonstrate the results with an application.